Epidemiological profile of sesamoid disorders of the first metatarsophalangeal joint - Hardt, Marcelo Rassweiler; Machado, Samuel; Demore, Andre Bergamaschi; Kim, Antônio; Camargo, Leandro Marcantonio; Barbosa, Carolina Claudino (Scientific Journal of the Foot & Ankle, 2018)
Objective: The objective of this study is to describe the epidemiological characteristics of patients with sesamoid disorders in a sample of patients treated in the Brazilian public health system. Methods: A retrospective study was performed by reviewing the electronic charts of foot and ankle outpatient consultations over the past 5 years, analysing variables such as sex, age, occupation, ethnicity, participation in sports, laterality, and affected sesamoid (medial or lateral). Results: Abnormalities in hallucal sesamoids occur more frequently in women (63/108), during the third decade of life (56/108), and in the medial sesamoid (74/108); 65.7% of the sample with these abnormalities participated in physical activity regularly. No significant relationship was observed with laterality or occupation. Conclusion: The most commonly affected patients were females, with a mean age of 23.7 years, who participated in physical activity frequently; the right side and medial sesamoid bone were the most commonly affected sites. Level of Evidence II; Prospective Study.